Comparison of Symptoms and Lung Function in Patients with Chronic Obstructive Pulmonary Disease (COPD) Receiving Monobronchodilators and Dual Bronchodilators - Lingga, Elfia Damaiyanti Br; Pandia, Pandiaman; Pradana, Andika (Journal of Society Medicine, 2024)
Introduction: In COPD treatment with a monobronchodilator or dualbronchodilator, can be assessed for the prognosis of therapy outcomes provided to monitor the impact of intervention and recovery of daily activities, prevent acute exacerbations, and improve the productivity of patient’s COPD. To determine the comparison between symptoms and lung function in patients with COPD disease receiving monobronchodilator and dual bronchodilator. Method: This study is a retrospective cohort study. The research sample consists of COPD patients undergoing treatment with monobronchodilator or dualbronchodilator for a minimum of 3 months or 3 treatment visits. Symptoms are measured using mMRC and lung function is measured using spirometry (FEV1). Results: The majority of patients are male (87.1%) and over 60 years old (62.4%), with the majority being smokers (84.7%), and the most common therapy being monobronchodilator (62.4%) and dual bronchodilator (37,6%). There are differences in symptoms and lung function in patients receiving monobronchodilator and dual bronchodilator. Conclusion: The dual bronchodilator is more effective in reducing mMRC values, improving by 96.3%, and increasing spirometry values. The average FEV1 value in spirometry for patients using the dualbronchodilator increased by 13,907%, while for the monobronchodilator, it decreased by 5.589%.